Establishment of an Open Information Platform for the National Sports Center in China - Zhao Zhen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In recent years, digital public services have evolved rapidly, garnering significant attention within the socio-cultural domain, particularly in the sports sector. A pivotal concern is how to effectively consolidate and disseminate public digital sports resources that are distributed nationwide. Addressing this, our study proposes the architectural design and pivotal technologies for a nationwide public digital sports resource sharing cloud service platform. This platform is specially tailored for the National Sports Center, aiming to enhance the digital engagement of the sports community and promote the open sharing of digital sports resources. By focusing on the sports context, we explore the interaction design principles of an online sports research public service platform from an academic research perspective, aimed at enriching the digital sports experience. Furthermore, we delve into the dynamics of sports communication in the era of big data, analyzing its characteristics, and the internal and external forces influencing these dynamics. The establishment of a robust public data open information platform for the National Sports Center is examined, highlighting the challenges and opportunities it presents for sports communication. This is posited as an effective strategy to navigate the evolving landscape of sports communication in the contemporary era.